Innovativeness as an emergent property: a new alignment of comparative and experimental research on animal innovation - Griffin, Andrea S. (Philos Trans R Soc Lond B Biol Sci, 2016)
Innovation and creativity are key defining features of human societies. As we face the global challenges of the twenty-first century, they are also facets upon which we must become increasingly reliant. But what makes Homo sapiens so innovative and where does our high innovation propensity come from? Comparative research on innovativeness in non-human animals allows us to peer back through evolutionary time and investigate the ecological factors that drove the evolution of innovativeness, whereas experimental research identifies and manipulates underpinning creative processes. In commenting on the present theme issue, I highlight the controversies that have typified this research field and show how a paradigmatic shift in our thinking about innovativeness will contribute to resolving these tensions. In the past decade, innovativeness has been considered by many as a trait, a direct product of cognition, and a direct target of selection. The evidence I review here suggests that innovativeness will be hereon viewed as one component, or even an emergent property of a larger array of traits, which have evolved to deal with environmental variation. I illustrate how research should capitalize on taxonomic diversity to unravel the full range of psychological processes that underpin innovativeness in non-human animals.